2017
DOI: 10.1016/j.socscimed.2017.06.035
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of associations among helping, health, and longevity

Abstract: How does helping behavior contribute to the health and the longevity of older helpers? From an evolutionary perspective, the ultimate cause may be rooted in ancestral parenting and grandparenting. These activities may have generalized to a neural and hormonal caregiving system that also enabled prosocial behavior beyond the family. From a psychological perspective, helping others may be associated with healthy aging, which, in turn, contributes to longevity as a proximate cause. Yet little is known about the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 51 publications
6
26
0
2
Order By: Relevance
“…In the within-individual analysis, however, the only association that remained significant showed that the number of difficulties with activities of daily living decreased over time among grandparents whose childcare frequencies had increased previously. In line with previous longitudinal evidence associating babysitting with improved health (Hilbrand, Coall, Meyer, et al, 2017) and increased exercise (Hughes, Waite, LaPierre, & Luo, 2007), these findings are consistent with the association between grandchild care and grandparental well-being working specifically through physical health. Clearly, the final word on this association is some time away.…”
Section: Interdisciplinary Perspectives: Building the Bridge Between supporting
confidence: 90%
See 1 more Smart Citation
“…In the within-individual analysis, however, the only association that remained significant showed that the number of difficulties with activities of daily living decreased over time among grandparents whose childcare frequencies had increased previously. In line with previous longitudinal evidence associating babysitting with improved health (Hilbrand, Coall, Meyer, et al, 2017) and increased exercise (Hughes, Waite, LaPierre, & Luo, 2007), these findings are consistent with the association between grandchild care and grandparental well-being working specifically through physical health. Clearly, the final word on this association is some time away.…”
Section: Interdisciplinary Perspectives: Building the Bridge Between supporting
confidence: 90%
“…In a mediation analysis using structural equation modelling, grandparenting and supporting others were associated with improved subsequent health, which was in turn associated with longevity. Subsequent health partially mediated the associations between grandparenting and supporting others and longevity, accounting for 22% of this relationship (Hilbrand, Coall, Meyer, Gerstorf, & Hertwig, 2017). Therefore, health is likely to be on this causal path; however, more detailed information exploring issues of motivation, emotion and relationship quality are required to fully understand the mechanisms involved.…”
Section: Interdisciplinary Perspectives: Building the Bridge Between mentioning
confidence: 99%
“…Caregivers who provided emotional support without burden had a better score in total quality of life, self-realization/pleasure and control/autonomy than those who did not exchange or did not receive emotional support, perhaps a favorable indication of the notion that solidarity provision and without rendering can benefit the well-being of older adults (2,33) . Only providing support is an indicator of risk to the welfare of seniors, especially when they are members of dysfunctional families or very lacking in resources, in such a way that older adults represent a financial source for them (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados de otro estudio sugieren que existen asociaciones entre ser abuelos y apoyar a otros con la mayor longevidad. (Hilbrand, Coall, Meyer, Gerstorf, & Hertwig, 2017).…”
Section: Psicológicosunclassified